Global Perspectives on Immunization Against SARS-CoV-2 During Pregnancy and Priorities for Future Research: An International Consensus Paper From the World Association of Infectious Diseases and Immunological Disorders - Abu-Raya, Bahaa; Madhi, Shabir A.; Omer, Saad B.; Amirthalingam, Gayatri; Giles, Michelle L.; Flanagan, Katie L.; Zimmermann, Petra; O’Ryan, Miguel; Safadi, Marco A.; Papaevangelou, Vassiliki; Maertens, Kirsten; Wanlapakorn, Nasamon; et al. (Frontiers in Immunology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in pregnancy is associated with a higher risk for severe morbidity and mortality when compared with infection in non-pregnant women of childbearing age. An increasing number of countries recommend immunization against SARS-CoV-2 in pregnant women. Recent studies provide preliminary and supportive evidence on safety, immunogenicity and effectiveness of coronavirus disease 2019 (COVID-19) vaccines in pregnant women; however, important knowledge gaps remain which warrant further studies. This collaborative consensus paper provides a review of the current literature on COVID-19 vaccines in pregnant women, identifies knowledge gaps and outlines priorities for future research to optimize protection against SARS-CoV-2 in the pregnant women and their infants.